Cirrhosis and Severe Acute Respiratory Syndrome Coronavirus 2 Infection in US Veterans: Risk of Infection, Hospitalization, Ventilation, and Mortality. Issue 1 (2nd June 2021) - Ioannou, George N.; Liang, Peter S.; Locke, Emily; Green, Pamela; Berry, Kristin; O'Hare, Ann M.; Shah, Javeed A.; Crothers, Kristina; Eastment, McKenna C.; Fan, Vincent S.; Dominitz, Jason A.
Abstract : Background and Aims: Whether patients with cirrhosis have increased risk of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and the extent to which infection and cirrhosis increase the risk of adverse patient outcomes remain unclear. Approach and Results: We identified 88, 747 patients tested for SARS‐CoV‐2 between March 1, 2020, and May 14, 2020, in the Veterans Affairs (VA) national health care system, including 75, 315 with no c irrhosis–S ARS‐CoV‐2‐negative (C0‐S0), 9, 826 with no cirrhosis–SARS‐CoV‐2‐positive (C0‐S1), 3, 301 with cirrhosis–SARS‐CoV‐2‐negative (C1‐S0), and 305 with cirrhosis–SARS‐CoV‐2‐positive (C1‐S1). Patients were followed through June 22, 2020. Hospitalization, mechanical ventilation, and death were modeled in time‐to‐event analyses using Cox proportional hazards regression. Patients with cirrhosis were less likely to test positive than patients without cirrhosis (8.5% vs. 11.5%; adjusted odds ratio, 0.83; 95% CI, 0.69‐0.99). Thirty‐day mortality and ventilation rates increased progressively from C0‐S0 (2.3% and 1.6%) to C1‐S0 (5.2% and 3.6%) to C0‐S1 (10.6% and 6.5%) and to C1‐S1 (17.1% and 13.0%). Among patients with cirrhosis, those who tested positive for SARS‐CoV‐2 were 4.1 times more likely to undergo mechanical ventilation (adjusted hazard ratio [aHR], 4.12; 95% CI, 2.79‐6.10) and 3.5 times more likely to die (aHR, 3.54; 95% CI, 2.55‐4.90) than those who tested negative. Among patients with SARS‐CoV‐2 infection, those with cirrhosis were more likely to be hospitalized (aHR, 1.37; 95% CI, 1.12‐1.66), undergo ventilation (aHR, 1.61; 95% CI, 1.05‐2.46) or die (aHR, 1.65; 95% CI, 1.18‐2.30) than patients without cirrhosis. Among patients with cirrhosis and SARS‐CoV‐2 infection, the most important predictors of mortality were advanced age, cirrhosis decompensation, and high Model for End‐Stage Liver Disease score. Conclusions: SARS‐CoV‐2 infection was associated with a 3.5‐fold increase in mortality in patients with cirrhosis. Cirrhosis was associated with a 1.7‐fold increase in mortality in patients with SARS‐CoV‐2 infection.